(untitled) (Medico Legal Update, 2020)
Introduction:-Sexual assaults are inhuman crimes against individual as well as the whole society. This study was thus initiated to obtain statistical pattern of sexual assaults pertaining to analyze various aspects including socio-demography and victim assailant relation, other relevant factors. Materials and Method:- Inclusion Criteria :-all the victims/sexual offence survivors examined at SMS Medical College, Jaipur during 1st January 2018 to 31st December 2018 Exclusion Criteria:- all the alleged cases of sexual offence whom consent could not be obtained. Results:- total 60 cases were studied. The mean age of the victims in present study was 20.98 years. 73.33% victims were from urban regions. 50% victims were educated. 70% victims in the present study were married. Most common place of commission of the crime was the victim’s own home (46.67%) . 43.34% victims reported within one week time period from the incidence. 88.33% victims were assaulted by a single person. 76.67% victims were assaulted by familiar persons. In 51.67% cases, the victim had been assaulted multiple times. In 85% cases, there was peno-vaginal intercourse. 71.67% cases had no injury in the present study. 3.33% victims got pregnant after the sexual assault. Conclusion:- Females of reproductive age group were the most common victims in the present study. Familiar persons committed the crime in most cases and victim’s home was the most common site of occurrence. There was delayed reporting of the crime in most cases which was the main reason for loss of vital trace evidences. Suggestions:- Strict adherence to protocols for medical examination of victims of sexual assaults should be mandatory. Sex education should be provided to school students of teenage to increase awareness regarding medical and legal issues related to such events to increase the reporting of this crime.